Temperature-Dependent Storage Stability and Shelf-Life Assessment Of Palmyra Blended Beverage - Behera, Saloman; Nayak, Binata; Parida, Shweta (International Journal of Membrane Science and Technology, 2023)
Nutraceuticals added ready to serve blended beverages was prepared from tender palmyra pulp and the storage study of the developed beverages was carried out in this research. Blended beverage was prepared by blending the tender palmyra pulp along with green chilly pulp and ginger extract. For each treatment the final TSS was adjusted to 12 °Brix (as per optimization) in the blended juice. After the finalization of the juice blend, the pasteurized juice was further packed with preservatives such as potassium meta-bisulphite and sodium benzoate at 300ppm. The Palmyra blended juice was stored under ambient (30±5 °C) and refrigerated condition (4±1 °C) in glass bottles. The effect of preservative treatment and storage condition on quality parameters during storage of PBJ was investigated for a period of 180 days. The quality parameters considered under study were biochemical, phytochemical, sensory and microbiological property. The palmyra blended juice with sodium benzoate performed best under both ambient and refrigerated storage conditions up to 90 and 180 days respectively.